The return of Twin Peaks : squaring the circle - Boulegue, Franck (Intellect Books, 2021)
Franck Boulègue's latest book about David Lynch and Mark Frost's famous television series focusing on the eighteen new episodes directed by Lynch for season 3, screened in 2017. It analyses the season from a variety of angles, giving special importance to readings from an intertextual, ontological and spiritual perspectives. 81 b/w illus.